A Hydraulic Model Investigation of Drifting Snow - Wuebben,James L. (1978)
A model investigation of drifting snow conditions was conducted in a hydraulic flume using a sand-water analog. Model results were evaluated to define modeling parameters that would allow quantitative correlation between measured prototype drift conditions and the model. The modeled structure was the standard plan snow fence designed by the Wyoming Highway Department and installed along Interstate Highway 80 in 1971. The performance of this system was documented by the Rocky Mountain Forest and Range Experiment Station of the U.S. Forest Service. Models of the fence were constructed for three heights and two geometric scales. Geometric scaling was based on terrain roughness and boundary layer thickness considerations, while velocity scaling was based on particle fall velocity and threshold of motion characteristics. Simulation of the atmospheric boundary layer was found to be of primary importance. Velocity scaling analysis suggested the use of a 'significant wind' concept based on a combination of velocity magnitude and frequency. Similarity of precipitation rate was not essential, and could be altered within limits to adjust the time scale. The response of the model to the shape of model elements was significant. Although the model is distorted and inexact similarity is achieved, it appears useful on a practical basis. (Author)